PENGOLAHAN BAHAN ALAMI UNTUK PENGEMBANGAN PRODUK TOTEBAG ECOPRINT DIDESA PRANTI KECAMATAN SEDATI KABUPATEN SIDOARJO: Ecoprint Dengan Teknik Pounding pada Totebag - Manik Ayu Titisari; Arifatus Zulha Aisjah (Universitas PGRI Adi Buana Surabaya, 2023)
Because it has a favorable effect on mothers - the mother herself - ecoprint training with the pounding technique, which was described to the women of the Family Welfare Empowerment (PKK) group in Pranti Village, Sedati District, Sidoarjo Regency, is an activity that needs to be carried out regularly between PKK women in Pranti village. This group of women initially displayed lower levels of daily productivity. Their daily activities changed after undergoing ecoprint instruction using the hammering technique. This training is delivered face-to-face in phases and includes briefing approaches, talks, handouts on the making process, and practice. Women from the PKK group can soon discover her instructions because the ecoprint process is less sophisticated, practical, and easier than the batik technique, and the tools and materials are readily available. Additionally, the materials used, especially different types of leaves, are easily accessible in the area surrounding the property. Tote bags, long fabrics, and clothing can all be produced using the outcomes of ecoprint training combined with the pounding process.